Koroid melanomunu taklit eden bir lezyon - (:unkn) unknown (My University, 2007)
Vitre içi kanamaya bağlı ani görme azalması ile şikâyeti ile kliniğimize başvuran bir olguda fundus muayenesi yapılamadığı için radyolojik tetkiklere başvuruldu. Ultrasonografi, doppler ultrasonografi, manyetik rezonans görüntüleme tetkikleri retinal lezyonun koroid melanomu ile uyumlu olabileceği şeklinde rapor edildi. Vitre içi kanamanın koroid melanomlarında nadir olması nedeniyle tanısal vitrektomi yapıldı. Vitrektomide arka kutupta diskiform lezyon tespit edildi.

Radiological evaluations were performed as fundus examination was unavailable due to intravitreal hemorrhage in a case who came to our clinic with the complaint of an acute vision loss. Ultrasonography, doppler ultrasonography and magnetic resonance imaging reported that the retinal lesion was compatible with malignant melanoma. The patient underwent diagnostic vitrectomy due to rarity of vitreous hemorrhage with choroidal melanomas. Retinal examination revealed disciform lesion during vitrectomy.
A lesion mimicking melanoma of choroid
Keywords: Tıbbi Araştırmalar Deneysel; Göz Hastalıkları; Periferik Damar Hastalıkları